Pengaruh Kredit Bermasalah Terhadap Rentabilitas Ekonomi Pada Koperasi Simpan Pinjam Balo’ Toraja Kecamatan Makale Kabupaten Tana Toraja - Wilma Dian Ardiyanti; Srisetyawanie Bandaso; Grynjiel Ayu Sandangan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the effect of non-performing loans on economic profitability in the Balo' Toraja Savings and Loans Cooperative, Makale District, Tana Toraja Regency. The type of research used in this research is quantitative descriptive research. The unit of observation in this research is the financial report and non-performing loans for 2016-2020. The results of this research show that there is an influence of non-performing loans on economic profitability, which means that if non-performing loans increase, economic profitability will decrease, and vice versa, if non-performing loans decrease, economic profitability will increase.